Tingkat Efisiensi dan Produktivitas Lembaga Zakat di Indonesia - Salman Al Parisi (Esensi: Jurnal Bisnis dan Manajemen, 2017)
Efficiency and Productivity Rate of Zakah Institution in IndonesiaThis study aimed to measure the efficiency and productivity of five zakah institutions. Calculation of efficiency level in this study are relative, not absolute. This Study consists of two methods: Data Envelopment Analysis (DEA), and Malmquist Productivity Index (MPI). There are 5 research objects, namely DD, BAZNAS, PKPU, YBM BRI and RZI with annual data 2005 to 2014. Furthermore, the lowest relative efficiencies level is DD (2010) amounted to 9.63%. In addition, approximately 80% of five OPZs increased the productivity. In the general, the main factor of inefficient of five zakat institutions from 2005 to 2014 was caused by distribution of zakah to ashnaf which still not optimal, then it cannot solve the poverty rate. Furthermore, it needs to increase collection and distribution of zakah fund amounted to 31.53% and 47.87%. Besides that it needs to decrease cost of socialization and operational cost amounted to 11.81% and 8.79%.DOI:  10.15408/ess.v7i1.3687